Study of contact dermatitis among Hospital cleaners in Kota Bharu, Kelantan - Nordin, Rusli; Abdullah, Hasniza; Choudary, Sahel Reza; Nouri, Nazmi Mohd; Winn, Than; Sadiq, Ayub (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2003)
Dermatological disorders are among ten major work-related illnesses. The maintenance and support staff of healthcare industries are particularly vulnerable to occupational exposures and cleaners have been identified as being at high risk for contact dermatitis. This study is aimed at determining the prevalence, knowledge (K), attitude (A) and practice (P), and risk factors of contact dermatitis in hospital cleaners. A cross-sectional study was undertaken in August 2001 to June 2002. A pilot study was undertaken to validate the KAP questionnaire. Two hundred and ninety seven hospital cleaners were recruited from Hospital USM (HUSM) and Hospital Kota Bharu (HKB). Data was collected using a (1) structured questionnaire comprising of 3 socio-demographic, 5 occupational, 25 K, 14 A and 14 P (KAP) regarding contact dennatitis; (2) medical history and clinical examination by a dermatologist; and (3) patch test. Allergic and irritant contact dermatitis was diagnosed based on a history of chemical exposure, clinical examination and patch testing: a positive patch test differentiated allergic from irritant contact dermatitis. Results indicated that the prevalence of contact dermatitis was 7.4% (95% CI 4.7% - 11.0%). Allergic contact dermatitis and irritant contact dermatitis constituted 41.2% and 58.8%, respectively of contact dermatitis. Majority of contact dennatitis involved thigh, leg and feet (50.0%). Putative chemical agents responsible for occupational allergic contact dermatitis were nickel sulphate (5 patch positives), rubber chemicals (1 mercapto mix patch positive), preservatives in soaps (1 paraben mix patch positive) and contaminants in soaps and detergents ( 1 potassium dichromate patch positive). Factor analysis of the KAP questions extracted the following common factors: K: causes, clinical features, treatment, and prevention; Aand P: health-seeking behavior, safe work practice, safety policy, and use of personal protective equipment (PPE). Reliability analysis indicated that the questions were internally consistent with Cronbach's alpha ranging from 0.46 to 0.97. There was no significant difference in the mean scores of KAP between 22 hospital cleaners with contact dermatitis and 275 hospital cleaners without. Simple logistic regression analysis showed that history of earlier hand eczema (Crude OR 8.24, 95% CI 3.31, 20.53), wearing protective glove for more than 2 hours per day (Crude OR 2.97 95% CI 1.17,7.55) and wet work for more than 2 hours (Crude OR 5.04, 95% CI 1.85,13.74) were significantly associated with contact dermatitis in hospital cleaners. Multiple logistic regression analysis showed that there was a positive association between the duration of use of protective glove for more than 2 hours and contact dennatitis (adjusted OR 3.29, 95% CI 1.03, 10.73). The odds ofhaving contact dermatitis was 8.79 times in hospital cleaners with a history of earlier hand eczema (adjusted OR 8. 79, 95% CI 3.15, 24.56). We conclude that prolonged use of protective glove and previous history of hand eczema were associated with contact dermatitis in hospital cleaners.